PC.101 Reducing catheter associated blood stream infections in neonatal intensive care. (9th June 2014) - Bunni, L; Brunskill, K; Parmar, R; Townley, P; Yoxall, B
Abstract : Background: Central vessel catheterisation (CVC) is commonly used during neonatal intensive care. Catheter associated blood stream infection (CABSI) is a serious complication of CVC. We introduced a care bundle to reduce CABSI in or unit. Aims: To determine the rate of CABSI within our unit, examine which types of CVC were most likely to develop CABSI and determine whether the care bundle had influenced CABSI rate. Methods: Retrospective survey using data from electronic patient records and microbiology database. CABSI was diagnosed using standard criteria. Results: In 2009 311 babies had 657 CVCs for 3992 catheter days (cd). In 2012, 292 babies had 682 CVCs for 3792 cd. No significant differences in patient demographics. Overall CABSI rate was 22.4/1000cd in 2009. The rate was higher in long line days (25/1000cd) than UVC days (17.5/1000cd). The highest rate was seen during days with multiple CVCs in situ (39/1000cd). The proportion of CVC days provided by long lines fell from 51% to 45% between 2009 and 2012 (p < 0.01). There was an increase in UVC days from 24% to 33% (p < 0.01). The overall CABSI rate was much lower at 6.1/1000cd in 2012. The proportion of babies who had a CVC and developed CABSI fell from 23% in 2009 to 7.5% in 2012 (p < 0.0001). Conclusion: We have seen a significant reduction in CABSI. Some of this can be attributed to the increased use of multi-lumen UVCs, although the magnitude of the effect suggests that other aspects of the policy changes are more important.